Power quality problems mitigation using dynamic voltage restorer (DVR) with pi controller and fuzzy logic controller - jaswini Sarwade, Te; S. Jape, V; G. Bharadwaj, D (International Journal of Engineering and Technology, 2018)
The existence of non-standard currents, frequencies and voltages enhances the Power Quality (PQ) problems. Power consumed by the consumers and losses occurred in power system are deciding factors for the utility to determine the performance of the power system in terms of Power Quality. These Power Quality problems lead to failure of end user equipments as well as creates disturbances in power distribution network, thereby deteriorates residual life assessment of major equipments used in substation. The PQ problems can be characterized as voltage surges, sags, swells, harmonic distortions, etc. There are many reasons for the determination of Power Quality. The loads used by the consumers of electricity abnormally leads to deprove the Power Quality. Low power factor loads are taken care of by the utilities in the form of financial penalty. However, occurrence of harmonics, voltage swells and sags in the system is the most powerful reason behind degradation of Power Quality. To mitigate these issues, use of Custom Power Devices (CPD) in the distribution network is the most significant solution. Paper presents the design of the CPD like Dynamic Voltage Restorer (DVR) using two control strategies i.e. PI Controller and Fuzzy Logic Controller (FLC). MATLAB/SIMULINK is used to analyze the effectiveness of these control strategies.Â